UDL-designed frameVR improves inclusive learning for university students with disabilities - Mendoza Velazco, Derling Jose; Quintero Arjona, Gisela Consolación (Jurnal Cakrawala Pendidikan, 2026)
This study examined the adjusted effect of a FrameVR learning intervention designed according to Universal Design for Learning (UDL) principles on the conceptual understanding of university students with disabilities, controlling for baseline performance through ANCOVA. A quasi-experimental design with pretest and posttest measures in two groups was employed. The first group used the FrameVR + UDL method and the second received traditional virtual instruction in Moodle. A total of 299 Early Childhood Education students from the National University of Education, Ecuador, participated in the 12-week intervention. An ANCOVA was conducted to adjust the final score according to the initial level. The results showed that adjusted posttest scores differed significantly between groups, with the FrameVR + UDL group demonstrating higher adjusted performance. The pretest accounted for substantial variance η²p = 0.305, which confirmed the relevance of the statistical adjustment. The control group did not show statistically significant changes, unlike the intervention group which showed additional improvement. This result can be attributed not only to using an immersive environment, but also to integrating it into an inclusive teaching architecture guided by UDL. The study provided local evidence of improved academic outcomes in inclusive university contexts.